Adherence to dietary recommendations is not associated with depression in two Swiss population-based samples. (June 2017) - Richard, Aline; Rohrmann, Sabine; Vandeleur, Caroline L.; Lasserre, Aurélie M.; Strippoli, Marie-Pierre F.; Eichholzer, Monika; Glaus, Jennifer; Marques-Vidal, Pedro; Vollenweider, Peter; Preisig, Martin
Abstract: Little is known about adherence to dietary recommendations and depression. Furthermore, dietary habits may differ among depression subtypes, which has not been evaluated previously. Two population-based Swiss studies, including 3620 individuals from PsyCoLaus and 11, 032 individuals from the Swiss Health Survey 2012 (SHS), were used to examine the associations between adherence to common dietary guidelines and odds of depressive disorders. In both studies, depression was assessed by validated instruments. Adherence to dietary recommendations were assessed by a semi-quantitative food frequency questionnaire (PsyCoLaus) and by single item questions (SHS). Logistic regression analyses were used to assess the association of adhering to dietary recommendations with depression. For the analyses of diet with depression subtypes maximum-likelihood multinomial (polytomous) logistic regression analyses were conducted. No association of adherence to dietary recommendations with current major depressive disorder (MDD) was observed in any of the two study populations except for adherence to fish consumption, which was positively associated with MDD in the SHS. For depression subtypes, statistically significantly positive associations of vegetable consumption and adherence to the 5-a-day recommendation with current unspecified and current melancholic MDD were found. In conclusion, we don't see consistent associations between adherence to dietary recommendations and MDD or subtypes of depression. Highlights: Little is known about the adherence to dietary recommendations and depression. Adhering to dietary recommendations is not associated with depression overall. Dietary habits differ by subtypes of depression. 5-a-day recommendation was associated with current unspecified- and melancholic depression.